Chemical Fingerprinting of Various Tea and Coffee Types Using SEM, UV-Visible and FTIR Spectroscopy - Ainur Awanis Mohd Badiazaman,; Mohammad Hafizudden Mohd Zaki,; Siti Maryam Mazlan,; Nik Nur Airyn Natasha Amran,; Amira Yasmin Mohd Nor Hisyam,; Nur Amirah Faeqah Mohd Fadli,; Nurul Huda Afrina Mohamad Shafizan,; Nor Alian Ruzlan, (Journal of Science and Technology, 2025)
Chemical fingerprinting provides a robust approach for characterizing and differentiating various types of tea and coffee based on their unique chemical profiles. In this study, Scanning Electron Microscopy (SEM), UV-Visible (UV-Vis) and Fourier Transform Infrared (FTIR) Spectroscopy were employed to analyze and compare chemical fingerprint various types of tea and coffee samples. The study analyzed green tea, black tea, chamomile tea and coffee samples due to their distinct composition and sources of natural antioxidant properties. SEM results showed the surface morphology for all samples is varied indicating the differences in the nature of raw material, processing, composition and surface characteristics of samples. UV-Vis spectroscopy revealed distinct patterns of chromophores observed in the UV region 250-300 nm associated with key compounds such as phenolic substances, flavonoids, methylxanthine compounds and caffeine. Additionally, FTIR spectroscopy demonstrated the fingerprint spectra and functional groups for all samples such as N-H stretching, O-H stretching, C=C aromatic ring and C-O stretching vibrations revealing compositional variations such as polysaccharides, polyphenols, sugars, caffeine, fatty acids and amino acids. The results recorded clear distinctions among various tea and coffee types. This study highlights the potential of combining SEM, UV-Vis and FTIR spectroscopy as a non-destructive, cost-effective, and comprehensive toolkit for the chemical profiling of various foods, offering valuable insights for quality assessment, authentication, and adulteration detection in the food industry.